2006
DOI: 10.1021/bi060395k
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Nuclear Magnetic Resonance Spectroscopic Features of the 1‘,4‘-Iminopyrimidine Tautomeric Form of Thiamin Diphosphate, a Novel Intermediate on Enzymes Requiring This Coenzyme

Abstract: Appropriate compounds were synthesized to create models for the 1',4'-imino tautomer of the 4'-aminopyrimidine ring of thiamin diphosphate recently found to exist on the pathway of enzymatic reactions requiring this cofactor (Jordan, F., and Nemeria, N.S. (2005) Bioorganic Chemistry, 33, 190−215). The N1-methyl-4-aminopyrimidinium compounds synthesized on treatment with a strong base produce the 1,4-imino tautomer whose UV spectrum indicates a maximum between 300−320 nm, depending on the absence or presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 29 publications
2
51
0
Order By: Relevance
“…This raises a significant complication in the interpretation of UV-VIS and CD data on ThDP enzymes. As we had reported, the enamine derived from aliphatic 2-oxo acids has a λ max near 295 nm [5,6], the 1',4'-imino tautomer of ThDP when enzyme-bound has a λ max between 300-310 nm with a positive CD band [19][20][21][22], and, as is here shown, acetolactate (or derivative derived from β-hydroxypyruvate), also gives rise to a positive or negative CD band with λ max of 300-302 nm (sign depending on the particular enantiomer) and a corresponding UV signal.…”
Section: Discussionmentioning
confidence: 71%
“…This raises a significant complication in the interpretation of UV-VIS and CD data on ThDP enzymes. As we had reported, the enamine derived from aliphatic 2-oxo acids has a λ max near 295 nm [5,6], the 1',4'-imino tautomer of ThDP when enzyme-bound has a λ max between 300-310 nm with a positive CD band [19][20][21][22], and, as is here shown, acetolactate (or derivative derived from β-hydroxypyruvate), also gives rise to a positive or negative CD band with λ max of 300-302 nm (sign depending on the particular enantiomer) and a corresponding UV signal.…”
Section: Discussionmentioning
confidence: 71%
“…In the N1′-methylpyrimidinium the pK a of the exocyclic amine is reduced to ca. 12-12.5 [38,47], offering rationalization for the presence of conserved glutamate as a catalyst for the amino ⇌ imino tautomeric equilibration.The first evidence for a spectroscopic signature for the IP tautomer was found by Sergienko on the slow E477Q YPDC variant [45]. In a series of studies, Zhang [45] and later Baykal [47] showed that an appropriate chemical model for the 1′,4′-iminopyrimidine will give rise to a UV absorption in the 300-310 nm range.…”
Section: Aii the 1′4′-iminopyrimidine (Ip) Form Of Thdp [2743-46]-mentioning
confidence: 99%
“…12-12.5 [38,47], offering rationalization for the presence of conserved glutamate as a catalyst for the amino ⇌ imino tautomeric equilibration.The first evidence for a spectroscopic signature for the IP tautomer was found by Sergienko on the slow E477Q YPDC variant [45]. In a series of studies, Zhang [45] and later Baykal [47] showed that an appropriate chemical model for the 1′,4′-iminopyrimidine will give rise to a UV absorption in the 300-310 nm range. Serendipitously, the 15 N chemical shifts of the three species on the left hand side of Schemes 1 and 2, the two neutral and one positively charged forms of the 4′-aminopyrimidine are quite distinct [47] (early 15 N NMR experiments were reported on this issue by J.D.…”
Section: Aii the 1′4′-iminopyrimidine (Ip) Form Of Thdp [2743-46]-mentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is unable to undergo dephosphonylation, and would presumably form a stable pre-decarboxylation analog of C2α-mandelylThDP (MThDP), the first covalent ThDP-bound intermediate in the decarboxylation of benzoylformate. In doing so, MBP might provide insight into the formation of intermediates with tetrahedral substitution at the C2α atom, including the state of ionization and tautomeric nature of the 4'-aminopyrimidine ring of ThDP on BAL, a major current focus of research of the Rutgers group with several collaborators (4)(5)(6)(8)(9)(10)(11)(12). We have now demonstrated in a number of ThDP-dependent enzymes that the 4'-aminopyrimidine ring of ThDP actively participates and plays a very crucial role in catalysis via its 1',4'-iminopyrimidine tautomeric form (4-7).…”
mentioning
confidence: 99%